Objek Wisata Religi: Potensi dan Dampak Sosial-Ekonomi bagi Masyarakat Lokal (Studi Kasus Pada Makam Syekh Mansyur Cikadueun, Pandeglang) - Saeful Fachri (FEB Universitas Sultan Ageng Tirtayasa, 2018)
Religion tour is a tradition which has last on the society. The religion tour destination in Pandeglang regency are very rich; one of them is Syekh Mansyur Cikadueun, as a religion tour which has potentially increased the standard of economy and social of local society at the area. The purpose of the research is to know the economy and social impact as the existence the religion tour object to the local society. It is seen that the economy impact on the tourism area, increasing job demand and the income of the house hold which directly engage in the tourism object. Whereas, the social impact can be seen the interaction between society and tourist, the perception of the tourist, the orientation of the local society to the religion tour object only for spiritual or has been replaced to the commercial means. The data of this research obtained; 1. the participative observation which the researcher, himself involved in getting the data. 2. Interviewing the society which is involved on the activity of the religion tour on the area.